Response of East African highland bananas and hybrids to Radopholus similis - Dochez, C.; Whyte, J.; Tenkouano, A.; Ortíz, R.; Waele, D. de (2005)
The burrowing nematode, Radopholus similis, is a serious threat to sustainable banana production worldwide. A promising way of controlling nematodes is through the development and deployment of resistant cultivars. This usually involves crossing triploid cultivars with fertile diploids to produce tetraploids that generally display greater male and female fertility. Selected tetraploids are then crossed with improved diploids to produce sterile secondary triploids. This study evaluates the host response of the most commonly grown East African highland bananas in Uganda. Also, the host responses of diploid hybrids and East African highland banana derived hybrids, including tetraploids and secondary triploids, were evaluated. The individual root inoculation method was used for screening the Musa accessions for resistance to R. similis. The final nematode population of each accession was compared with the final nematode population of a susceptible reference cultivar, Valery, and with the final nematode population of a resistant reference cultivar, Yangambi km5. Results show that, except for cv. Muvubo, East African highland bananas were as susceptible to R. similis as cv. Valery. Four out of 13 tetraploid hybrids were identified with resistance to R. similis, as well as 13 out of 19 diploids and five out of 18 secondary triploids.